Voices of Resistance : Interdisciplinary Approaches to Chican@ Children's Literature. - Alamillo, Laura (Rowman & Littlefield Publishers, 2017)
This edited volume offers an interdisciplinary and expansive analysis of Chican@ children's literature in light of current political, social, and cultural trends.